Respuesta :

Answer:

x = -9/5

y = 16/5

Step-by-step explanation:

-3x-2y=-1            first you need to multiply the numerator by 3 so when adding

4x+6y=12           the y's cancel and you get a single variable

3(-3x-2y=-1)     —>  -9x - 6y = -3     then you add the like terms

 4x+6y=12      —>   4x + 6y = 12

(-9x+4x) + (6y - 6y) = (-3 + 12)

-5x = 9  then you divide by -5

x = -9/5

then you plug this in to either equation

4(-9/5) + 6y = 12

-36/5 + 6y = 12   then you add 36/5 to both sides

6y = 96/5  then you divide by 6

y = 16/5